HUBUNGAN PENGETAHUAN DENGAN PERILAKU PENGGUNAAN GREEN PACKAGING DI MASYARAKAT DKI JAKARTA - Anisa Nuraini Priambudi; Yosini Deliana (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
DKI Jakarta is a metropolitan city which is well-known as a flood subscriber and ranks number 1 as the region with the most waste in Indonesia. Various attempts have been done by the government to reduce the use of plastic as one of the waste that is difficult to decompose, both in the form of appeals to regulations. This study aims to determine the relationship of knowledge with the use of green packaging behavior in the people of DKI Jakarta. This research is a quantitative research using survey method and Pearson correlation analysis. The analysis shows that the higher level of public knowledge about green packaging will have a good effect on the behavior of using green packaging. The dominant factor that is considered by the public in recognizing and using green packaging is environmental care, social media and the surrounding social environment. Many people have already know about the Regulations of the Governor of DKI Jakarta Number 142 Year 2019 regarding the obligation to use environmentally friendly shopping bags at shopping centers, supermarkets and people's markets.  In addition, the community is willing to start switching to green packaging little by little, such as carrying their own shopping bags, drinking bottles and lunch boxes, and educating people around them to do the same.